Thinking beyond extremism: a critique of counterterrorism research on right-wing nationalist and far-right social movements - Tetrault, Justin Everett Cobain (The British journal of criminology, 2022)
Researchers increasingly use counterterrorism approaches to explain how right-wing groups mobilize as a growing social movement. I reveal the limits of security-oriented research for studying right-wing movements using a semi-ethnographic case study of the Canadian yellow vests. Dominant security narratives paint Canada’s yellow vests as foremost a criminogenic and violent white nationalist movement. My findings, however, suggest that these groups (1) fetishize law and order; and (2) attempt to maintain legitimacy by rejecting vigilantism and policing extreme messaging. Fixating on the ‘extremism’ and criminal risks of right-wing movements can distort analysis and exaggerate their distance from mainstream culture. My data include over 40 h of participant-observation at 20 right-wing rallies and 35 interviews with current leaders and members of on-the-ground nationalist groups.